Clinical Aspects of HyFoSy as Tubal Patency Test in Subfertility Workup. (8th July 2019) - Exalto, Niek; Emanuel, Mark Hans
Abstract : Background . Tubal patency testing is an essential part of female subfertility evaluation. Traditionally, hysterosalpingography (HSG) was the first step to evaluate tubal patency. However, during the past decade Hysterosalpingo-Contrast Sonography (HyCoSy) was introduced in order to avoid radiation exposure and Hysterosalpingo-Foam Sonography (HyFoSy) has been developed as a safe and less painful alternative. Objectives and Rationale . The aim of this narrative review is to provide an overview of the currently available HyFoSy literature and related clinical aspects. Search Methods . A literature search was conducted using PubMed and Embase from the introduction of HyFoSy to March 2019. Unfortunately, a meta-analysis was not possible due to a too small number of studies, being mutually incomparable for the various subjects of clinical aspects, even for the reliability as a test for tubal patency. Outcomes . Nine small studies concluded that the accuracy and effectiveness as a test for tubal patency of 2D- and 3D-HyFoSy are comparable or even better than HSG or HyCoSy. With or without using Doppler techniques, 3D-HyFoSy does not seem to offer benefits above real-time 2D-HyFoSy. Five studies reported on pain and discomfort during HyFoSy, concluding that HyFoSy is a well-tolerated, less painful procedure compared to HSG, without a need for the use of analgesics. There are suggestions about an increased pregnancy rate in the first three cycles after the procedure but in no studies pregnancy outcome after HyFoSy was compared with other or no intervention. Wider Implications . HyFoSy is a promising and safe alternative for HSG with regard to accuracy and effectiveness. HyFoSy lacks radiation and iodine exposure and is a well-tolerated and less painful procedure than HSG, without the need for analgesics. However more research is needed to make clear statements regarding a therapeutic effect of HyFoSy.